URGENSI PELESTARIAN DAN REHABILITASI MANGROVE BAGI MASYARAKAT DESA PANTAI MEKAR KECAMATAN MUARA GEMBONG - Ahnanto Ahnanto; Erry Syahpirudin; Indra Purba Waskita; Novita Novita; Sri Hartati; Awaluddin Tjala; Muhammad Zid Zid (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2014)
ABSTRACT This study aimed to determine the role, functions and benefits of mangrove forests to people's lives, causing damage to mangrove ecosystems, as well as the efforts of preservation and rehabilitation of mangrove ecosystems, which have been, are being and will be done in the future in the village of Desa Pantai Mekar, Muara Gembong. This type of study is a qualitative research approach and deep insight into the survey with a view to understanding social situations, events, roles, or groups of specific interactions. This study uses a variety of techniques and a variety of instruments to collect data. Data analysis using descriptive qualitative techniques. The results of the study were researchers from interviews get to the informant, discovered a few things related to the condition of the village before 1980 are as follows: (1) water of Citarum river can still be used to meet the needs drinking and cooking water. The condition water of Citarum River is still clean and healthy so there are no complaints about sore skin. (2) Harmonization ecosystem around Citarum River is still well preserved. Mangrove forests are broadly useful as a bastion of protection of coastal areas from the impact of flooding. (3) Prior to 1980, people never feel the flood, vast mangrove forests also provide benefits to fishermen because under mangrove forests store a lot offish habitat so that fishermen catch fish gained a lot and easy. This study gives the conclusion that mangrove forests have a role, function and great benefits to people's lives Desa Pantai Mekar, Kecamatan Muara Gembong. The cause of the destruction of mangrove forests on there, due to occupational mangrove ponds, agricultural, residential location, fulfilling the need for firewood by the citizens, abuse of authority by purchasing land illegally forestry, forestry lack of supervisory personnel. Mangrove rehabilitation efforts have not been accompanied by proper preservation. The parties directly benefit from mangrove deforestation, not to replant immediately. Keywords: mangrove forests, the urgency of preservation, rehabilitation.